Pelatihan Pembuatan Deobalm Alami ‘Nature Deobalm’ di Laboratorium Entrepreneurship UIN Palangka Raya - Noor Hujjatusnaini (Jurnal Pelayanan Masyarakat, 2025)
This community service program aims to enhance students’ knowledge and awareness regarding natural cosmetic formulations through training on the development of a natural deodorant balm, “Nature DeoBalm.” The activity was conducted at the Entrepreneurship Laboratory of UIN Palangka Raya and involved fifth-semester students of the Biology Education Department as participants. The training integrates promotive and applicative approaches, combining theoretical education on the risks of synthetic deodorants with direct observation of the production process for natural deodorant balm. The program emphasized the use of safe, plant-based ingredients such as beeswax, coconut oil, shea butter, vitamin E, and essential oils, which are known for their antibacterial, moisturizing, and skin-protecting properties. The implementation included several stages: preparation, material presentation, demonstration of the formulation process, product observation, evaluation, and documentation. Results showed that students demonstrated increased understanding of natural cosmetic components, formulation techniques, and the benefits of natural deodorants. They also developed a heightened awareness of environmentally friendly personal care products and showed interest in exploring entrepreneurial opportunities in herbal-based cosmetics. This program highlights the importance of introducing natural cosmetic innovation in higher education environments as a way to build scientific literacy, practical skills, and entrepreneurial competence. Overall, the activity successfully provided meaningful learning experiences and promoted the utilization of natural ingredients as sustainable alternatives to synthetic deodorant products.